Issues and Concerns of Teachers in Mindanao State University-Sulu Towards Modular Distance Learning Approach - Alvarez, Michelle Y. (HM Publisher, 2021)
The modular distance learning approach (MDLA) involves individualized instruction that allows learners to use self-learning modules (SLMs) in print or digital format/electronic copy. This study aimed to investigate on the issues and concerns of the Mindanao State University-Sulu teachers on the modular distance learning approach. This research was a descriptive study. The location of the study was at Mindanao State University-Sulu, Philippines. There were 48 teachers who served as respondents from different colleges of Mindanao State University-Sulu. The respondents were given enough time to answer the questionnaire, after which the questionnaires were collected immediately. The participants agreed that they failed to communicate and guide the students easily due to poor internet access, in which they inevitably encountered discourteous attitudes from the students. Teachers admitted that they receive inappropriate approaches and complaints if the students do not understand the modules, which eventually leads to not receiving the answer sheets on time. In conclusion, The issues encountered towards the modular distance learning approach were communication failure like that of instructions or confusion of students on the modules, limited teacher guidance, student’s discourteous approach to teachers, complaints about not understanding the module, and all of which results to misbehavior on students and failure to pass worksheet on time.